Biodiversity Assessment of a Fringing Reef in Palk Bay, India - Sukumaran, Sandhya; George, Rani Mary; C., Kasinathan (Fishery Technology, 2025)
Kathuvallimuni Reef, a fringing reef of Palk Bay was surveyed for the assessment of the coral cover and biodiversity during January-May 2005, following the Line Intercept Transect Method and their geographical positions were fixed using the Global Positioning System. The percentages of live and dead coral cover at each site were derived. A total of 20 hard coral species were found on the transects; Platygyra lamellina was the major species at 3 sites, followed by Porites solida, Favites virens, Hydnophora exesa, H. microconus,Â Turbinaria mesenterina, Acropora hyacinthiis and A. corymbosa at each of the 7 sites. The total live and dead coral cover for the reef as a whole was estimated as 37.8% and 32.6% respectively and the remaining part was covered with seagrasses, sand and rubble. Dead coral cover was dominated by poritids. Further, relative abundance values were derived for each species and they were assigned status as dominant/abundant/common/uncommon/rare. P.lamellina belonged to the category "abundant" and all other species were either of "common" or " uncommon " status only. The Shannon indices of diversity in most of the sites were moderate varying from 1 to 2 and the reef as a whole showed a diversity of 2.8. The species richness and evenness values showed values of 5.23 and 0.9 respectively.